Registration and Blocking of Tax Bill / Calculation of Adjustments: New Rules for Business and Fiscal Officers - O. А. Yurchenko; О. А. Svyryda (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2018)
Implementation of the system for administering value added tax for the domestic business sector was an IMF requirement. However, its applications by business entities could not eliminate “tax heavens”, barter deals and purchase (sale) of doubtful tax credit. It was in 1 July 2017 that the system for computerized monitoring of the conformity of tax bills (TB) / calculation of adjustment (CA) to the risk assessment criteria sufficient to stop registration of such TB / CA in the Single Register of Tax Bills was launched. The article’s objective is to form the authors’ vision of the essence of the problem related with registration and blocking of TB and CA in the Single Register of Tax Bills. The following aspects are covered by the analysis: the nomenclature of indicators checked in TB / CA deciphered upon coming to the State Fiscal Service of Ukraine; the types of receipts on the results of computerized check, intended for VAT payers; the detailed list of criteria for exclusion of TB / CA from the monitoring by the State Fiscal Service of Ukraine (once these criteria are not met, TB / CA is to become subject to monitoring and check for the riskiness of taxpayer and its operations, i. e. the criteria of fictitious business); the indicators of the positive story of a taxpayer. The issues of identifying the taxpayer risks that can be subject to scrutiny by the State Fiscal Service are highlighted. The criteria determining the positive tax story of a taxpayer are given.It is concluded that all the TB and CA submitted for registration in the Single Register of Tax Bills are to be checked for the conformity to three legally defined essential criteria; once TB / CA does not meet these criteria, they will be subject to monitoring and check for conformity with the criteria of riskiness of taxpayer and operations and the indicators of positive taxpayer story. The positive taxpayer story can rescue a VAT payer from blocking of its TB / CA that meet the riskiness of operation criterion. But once a taxpayer gets on the list of risky business entities, registration of its TB / CA will always be blocked.